GC-MS ANALYSIS AND MOLECULAR DOCKING STUDIES OF LASERPITIUM LATIFOLIUM L EXTRACT FOR ANTI-DIABETIC ACTIVITY - MUKKA, DIVYA; DEVARAKONDA, KRISHNA PRASAD (International Journal of Applied Pharmaceutics, 2025)
Objective: To assess the anti-diabetic activity of Laserpitium latifolium l extract through computational docking studies. Methods: Crude extract of Laserpitium latifolium l whole plant was obtained using a rotary evaporator. The extract was analyzed for bioactive compounds using Gas chromatography/Mass spectrometry (GC-MS). The extract was examined for their anti-diabetic effects through computational docking studies and in vitro. For docking studies, proteins of diabetes mellitus, α-amylase and α-glucosidase, were selected from the literature. Results: Binding affinity assessed by score function identified 2,4-Thiazolidinedione, 5-[[4-(4-pyridinyl)-6-quinolinyl] methylene]-(5Z)-(highest docking score of-7.8 kcal/mol) and cycloartenol acetate (docking score of-7.5kcal/mol) are the most promising compounds that showed strong affinity to target proteins of diabetes mellitus. These compounds have the highest docking scores, suggesting that they are potential candidates for anti-diabetic drug development. Extract of L. latifolium exhibited 68.1% potent activity at 250 μg/ml. Conclusion: In the anti-diabetic potential of crude extracts, multiple pancreatic and extra-pancreatic mechanisms may occur synergistically to achieve a strong anti-diabetic effect.